Recent Patents Review on Electrodeionization - Wang, Jianyou; Fan, Gaixiao; Dong, Heng; Fei, Zhaohui; Chen, Weili; Lu, Huixia (Recent Patents on Chemical Engineering, 2011)
The recent patents and progress of electrodeionization (EDI) in fields of water deionization and wastewater treatment are reviewed in the present paper. The discussion focuses on such major aspects: applied ion exchange media, inner configuration and operation manner of the EDI, integrated membrane processes based on EDI and new applications of the technology. As the newest outstanding technology for water deep desalting, EDI has been widely used for ultrapure water production in many industries and laboratories together with important improvements in recent years. Durative advancements have been achieved by inventors such as more even current distribution, higher contact efficiency between water and ion exchanger, more effective precipitation preventing and lower energy consumption. Besides, some improvements also have been achieved in other new fields in addition to pure water production. The application in water softening, seawater desalination and wastewater treatment were introduced for example. It is believed that the electromembrane process of EDI will play an important role in water desalting, wastewater reclamation and cleaner production of chemical engineering near future.
Keywords: Electrodeionization